Socialization And Practice Of Making Moringa Leaf Pudding As A PMT Innovation In Balung Kulon Village: Sosialisasi Dan Praktik Pembuatan Puding Daun Kelor Sebagai Inovasi PMT Di Desa Balung Kulon (JURNAL UNEJ, 2023)
The quality of nutrition determines the growth of toddlers. Fulfillment of food quality utilizing local food ingredients is an alternative that can be developed to be able to produce more innovative food variations. One way to deal with nutritional problems is to provide high-energy and protein Supplementary Feeding (PMT) to toddlers according to their nutritional needs. The Collaborative KKN activity carried out in Balung Kulon Village offered the idea of ​​making Moringa leaf pudding as a PMT innovation because of the nutritional content in Moringa leaves and the ease of finding these leaves at the KKN activity location. After getting an idea, the students who were members of the Collaborative KKN held discussions and coordinated with the village government, village midwives and stunting cadres to carry out socialization activities as well as practice making Moringa leaf pudding. The schedule of activities will be held on July 29, 2023. The activity begins with socialization carried out by student members of the KKN to provide an understanding of the nutritional quality contained in Moringa leaves and then continues with the practice of making Moringa leaf pudding. The purpose of this implementation is to help the success of government programs in reducing stunting rates in Balung Kulon Village, Balung District, Jember Regency and to increase community skills in innovating food offerings to increase nutritional intake. The method of this implementation is by way of socialization and training on how to make moringa pudding products. The results of this implementation are expected to provide new references that increase the understanding of cadres and parents of toddlers or the community regarding PMT menu innovations.